2020
DOI: 10.3390/w12030783
|View full text |Cite
|
Sign up to set email alerts
|

Net Ecosystem Production of a River Relying on Hydrology, Hydrodynamics and Water Quality Monitoring Stations

Abstract: Flow and water quality of rivers are highly dynamic. Water quantity and quality are subjected to simultaneous physical, chemical and biological processes making it difficult to accurately assess lotic ecosystems. Our study investigated net ecosystem production (NEP) relying on high-frequency data of hydrology, hydrodynamics and water quality. The Kanawha River, West Virginia was investigated along 52.8 km to estimate NEP. Water quality data were collected along the river using three distributed multiprobe sond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Hourly estimations of flow in the Kanawha River in the two locations (Q1 and Q2) were deduced from a developed and calibrated HSPF hydrologic model (Rojano et al, 2020). The Q2 differed with respect to Q1 due to the additional 4,290.4 km 2 of drainage area to the Kanawha River.…”
Section: High-frequency Data Of a Hydrologic Model And Water Quality ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Hourly estimations of flow in the Kanawha River in the two locations (Q1 and Q2) were deduced from a developed and calibrated HSPF hydrologic model (Rojano et al, 2020). The Q2 differed with respect to Q1 due to the additional 4,290.4 km 2 of drainage area to the Kanawha River.…”
Section: High-frequency Data Of a Hydrologic Model And Water Quality ...mentioning
confidence: 99%
“…The Q2 differed with respect to Q1 due to the additional 4,290.4 km 2 of drainage area to the Kanawha River. Also, the additional drainage area in Q2 has favored the increase of flow up to 17% when compared to Q1 (Rojano et al, 2020).…”
Section: High-frequency Data Of a Hydrologic Model And Water Quality ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that streamflow is expected to increase under the low-emission and decrease under the high-emission climate change pathway. In related work, Rojano et al [14] showed that modeled urban flow regimes were correlated to net ecosystem production (NEP), and under hypoxic conditions, local inflows were correlated with specific conductance. Results show the value of using integrated modeling approaches with observed data to resolve big-river challenges.…”
Section: Experimental Study Designs and Modelingmentioning
confidence: 99%